SHEVCHENKO AS LIBERTY - Protsiuk, S. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This essay-sketch reveals receptive essence of Taras Shevchenko’s image from the point of view eternity, namely from the perspective of the XXIst century.